MODERN APPROACH TO OPTIMIZATION OF ANESTHESIA IN DISEASES OF THE CENTRAL NERVOUS SYSTEM - Deekshith Battu (Journal of Science in Medicine and Life, 2024)
U Patients with a history of acute cerebrovascular accident (ACVA) should be assessed for perioperative stroke risk. A history of ACVA is one of the main risk factors for perioperative stroke; management of this category of patients, including preoperative preparation, can be carried out jointly with a neurologist if necessary. It is necessary to establish the etiology of ACVA, and it is desirable that sufficient time has passed since the stroke to restore autoregulation of cerebral blood flow - from 1 to 3 months. Patients who have suffered a stroke often receive long-term therapy with drugs that affect the hemostasis system, as well as β-blockers and statins, which reduce tolerance to bleeding, anemia and arterial hypotension. Currently, when choosing anesthesia method are taken into account in this category of patients with a history of stroke about the possible negative impact of anesthesia on the risk of cerebral complications. Maintaining systemic arterial pressure is one of the main tasks in patients with a history of stroke. It should be remembered that the percentage of its decrease from the initial value is a much more important guideline for assessing the development of hypotension than the absolute value. Studies show that a decrease in mean arterial pressure by more than 30% from the initial value is associated with the risk of stroke. Current evidence suggests that the use of neuraxial anesthesia techniques is associated with a reduced risk of perioperative CVA in high-risk proctology patients